Product Innovation Strategy and Its Influence on Growth of Fast-Moving Consumer Goods Manufacturing Firms in Nairobi County, Kenya - Khetia Nidhi Arvind; Francis Kijogi Mutegi (CV. Doki Course and Training, 2025)
Innovation is crucial for the growth of the Fast-Moving Consumer Goods (FMCG) manufacturing sector. This study investigates the impact of various innovation strategies on business performance within FMCG firms in Nairobi County, Kenya. The identified strategies include product innovation, market innovation, technological innovation, and process innovation. The problem addressed is the lack of understanding of how these strategies affect growth indicators such as revenue, market share, and operational efficiency in this region. A descriptive research design was employed. The target population comprised 204 employees from 51 FMCG manufacturing firms in Nairobi County, Kenya. A sample of 182 respondents was surveyed using a structured questionnaire. SPSS was used to analyse the data through descriptive and inferential statistics. The results showed that most of firms did not introduce new products, demonstrating a limited commitment to product innovation. The results revealed that product innovation had a significant influence on growth of fast-moving consumer goods manufacturing firms in Nairobi County, Kenya. The study concludes that product innovation strategy is essential in steering growth of the FMCG manufacturing firms in Nairobi City County, Kenya. It is recommended that the management team in FMCG manufacturing firms have a duty to introduce new products and enhance the existing products as a way of supporting continued growth of their firms.